Novel polymorphisms in caspase-8 are associated with breast cancer risk in the California Teachers Study. Issue 1 (December 2016) - Park, Hannah; Ziogas, Argyrios; Chang, Jenny; Desai, Bhumi; Bessonova, Leona; Garner, Chad; Lee, Eunjung; Neuhausen, Susan; Wang, Sophia; Ma, Huiyan; Clague, Jessica; Reynolds, Peggy; et al.
Abstract Background The ability of tamoxifen and raloxifene to decrease breast cancer risk varies among different breast cancer subtypes. It is important to determine one's subtype-specific breast cancer risk when considering chemoprevention. A number of single nucleotide polymorphisms (SNPs), including one incaspase-8 (CASP8 ), have been previously associated with risk of developing breast cancer. Because caspase-8 is an important protein involved in receptor-mediated apoptosis whose activity is affected by estrogen, we hypothesized that additional SNPs inCASP8 could be associated with breast cancer risk, perhaps in a subtype-specific manner. Methods Twelve tagging SNPs ofCASP8 were analyzed in a nested case control study (1, 353 cases and 1, 384 controls) of non-Hispanic white women participating in the California Teachers Study. Odds ratios (ORs) and 95 % confidence intervals (CIs) were calculated for each SNP using all, estrogen receptor (ER)-positive, ER-negative, human epidermal growth factor receptor 2 (HER2)-positive, and HER2-negative breast cancers as separate outcomes. Results Several SNPs were associated with all, ER-positive, and HER2-positive breast cancers; however, after correcting for multiple comparisons (i.e., p < 0.0008), only rs2293554 was statistically significantly associated with HER2-positive breast cancer (OR = 1.98, 95 % CI 1.34-2.92, uncorrectedp = 0.0005). Conclusions While our results forCASP8 SNPs should be validated in other cohorts with subtype-specific information, we conclude that some SNPs inCASP8 are associated with subtype-specific breast cancer risk. This study contributes to our understanding ofCASP8 SNPs and breast cancer risk by subtype.